2008
DOI: 10.1108/09615530810846365
|View full text |Cite
|
Sign up to set email alerts
|

Analysing an adaptive finite volume for flow in highly heterogeneous porous medium

Abstract: PurposeThis paper seeks to develop an adaptive finite volume algorithm, and to present an extensive numerical analysis of it.Design/methodology/approachThe effectiveness of the developed algorithm is demonstrated through practical and computationally challenging problems. The algorithm is tested for a wide range of singularities.FindingsThe convergence of the presented algorithm is independent of the regularity of the problems. It is shown that the our algorithm produces more accurate and well conditioned matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…For the numerical methods, we use finite volume methods for the space discretization (see [14,15]), and for the time discretization, we apply first order explicit or implicit Euler methods and second order CrankNikolson (CN) methods. For accurate results, we choose the second order CN method and accept the longer computational times, which are then needed.…”
Section: Numerical Methods For the Transportreaction Equationmentioning
confidence: 99%
“…For the numerical methods, we use finite volume methods for the space discretization (see [14,15]), and for the time discretization, we apply first order explicit or implicit Euler methods and second order CrankNikolson (CN) methods. For accurate results, we choose the second order CN method and accept the longer computational times, which are then needed.…”
Section: Numerical Methods For the Transportreaction Equationmentioning
confidence: 99%
“…To solve both the Darcy–Stokes and Stokes–Brinkman models, we have used well established mixed finite element formulation although other finite‐volume type approaches can also be used . The mixed finite element method has more than one approximation space and uses both the fluxes and the pressure as primary unknowns simultaneously, whereas in finite element and finite volume methods, fluxes are computed from the discrete pressure in a post processing step.…”
Section: Mathematical Modeling Of Multiscale Vuggy Mediummentioning
confidence: 99%
“…Reservoir simulation for oil/gas recovery is essentially a complex multi-phase, multi-component flow, heat and mass transfer problem (Lewis and Schrefler, 1998). The characteristics of a multi-phase flow deviate strongly from that of a single-phase (Gorji and Ghorbani, 2008) and there are additional difficulties in modelling and numerical simulations (Khattri, 2008). Several simulation studies on heat and mass transfer in hydrate filled porous media during decomposition induced by electromagnetic heating (Islam, 1994;Nasyrov et al, 1997) and microwave radiation (Sysoev and Kislitsyn, 2011;Wang et al, 2020;Zhao et al, 2016) have been reported.…”
Section: Introductionmentioning
confidence: 99%